UNDERSTANDING THE DANGERS OF HYPERTENSION IN THE PRODUCTIVE AGE THROUGH COMMUNITY EMPOWERMENT: MEMAHAMI BAHAYA HIPERTENSI PADA USIA PRODUKTIF MELALUI PEMBERDAYAAN MASYARAKAT - Isni, Khoiriyah; Nur Laily, Silvia; Auliya, Iffah; Widyapuspita, Tiara; Nur Aziziah, Erviana; Solikhin, Mukhamat; Fikri Wahyudi, Muhamad (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: Elevated blood pressure above the threshold is known as hypertension and is a contributing factor to cardiovascular disease. Lack of knowledge and inadequate physical activity were identified as the main factors contributing to hypertension among 36 individuals in the Padukuhan Jomblangan community of Bantul. This phenomenon occurs not only in old age but also in individuals of productive age. If health intervention is not carried out, sufferers may increase. Objective: To encourage public awareness regarding the prevention of hypertension through blood pressure-checking activities and health education. Method: This program aims to assist individuals with hypertension in Padukuhan Jomblangan, Bantul. To address hypertension, the program utilized health education, blood pressure screenings, and the incorporation of celery plants into family gardens. Health education is carried out through lectures, discussions and questions and answers. Data from blood pressure examinations is processed by comparing it with standards set by the Ministry of Health. Results: 13 people were identified as having level 2 hypertension, and 11 people were identified as having level 1 hypertension. The community was motivated to combat high blood pressure through physical activity, celery consumption, and growing celery at home for its medicinal properties. Conclusion: Stakeholders and Community Health Centers must revitalize NCDs Health Program to prevent NCDs. Furthermore, people can add celery as a family medicinal plant to reduce hypertension.